2006
DOI: 10.1128/mcb.02193-05
|View full text |Cite
|
Sign up to set email alerts
|

MafG Sumoylation Is Required for Active Transcriptional Repression

Abstract: A straightforward mechanism for eliciting transcriptional repression would be to simply block the DNA binding site for activators. Such passive repression is often mediated by transcription factors that lack an intrinsic repressor activity. MafG is a bidirectional regulator of transcription, a repressor in its homodimeric state but an activator when heterodimerized with p45. Here, we report that MafG is conjugated to SUMO-2/3 in vivo. To clarify the possible physiological role(s) for sumoylation in regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…pIM-His-MafG XB and pIM-His-MafG⌬C XB were used as expression vectors for MafG and MafG⌬C. pIM-His-MafG XB was described previously (33). pIM-His-MafG⌬C XB was generated by inserting the XbaIBamHI fragment of pET15b-MafG1-123 (23) into the NotI-NotI fragment of pIM-LacZ (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pIM-His-MafG XB and pIM-His-MafG⌬C XB were used as expression vectors for MafG and MafG⌬C. pIM-His-MafG XB was described previously (33). pIM-His-MafG⌬C XB was generated by inserting the XbaIBamHI fragment of pET15b-MafG1-123 (23) into the NotI-NotI fragment of pIM-LacZ (29).…”
Section: Methodsmentioning
confidence: 99%
“…Defective NF-E2 activity in MafG-null megakaryocytes is restored when MafG or MafK is exogenously expressed from a transgene driven by the Gata1 hematopoietic regulatory domain (G1HRD), which is active specifically in erythroid cells and megakaryocytes in vivo (30). Based on this result, we tested a sumoylation-defective MafG mutant, MafG K14R, by generating transgenic mouse lines expressing MafG K14R (33). The transgene-expressed mutant rescued defective NF-E2 activity in MafG-null megakaryocytes, and we concluded that MafG sumoylation is not essential for NF-E2 activity in normal megakaryocytes.…”
mentioning
confidence: 99%
“…The latter is generally mediated through recruitment of repressors by direct protein-protein interaction with the sumoylated protein on target promoters (60). For example, sumoylation of Elk1 (11,61), androgen receptor (62), MafG (63), and KAP1 (64) promotes association of these factors with HDACs, leading to gene silencing. However, the situation with Bcl11b is rather different.…”
Section: Discussionmentioning
confidence: 99%
“…C-terminal MafB-green fluorescent protein (GFP) fusion constructs were generated by PCR-mediated in-frame cloning of wild-type or mutant MafB into pEGFP-N1 (Clontech). PMI10 was used as an expression plasmid for E26 v-Myb (34).…”
Section: Methodsmentioning
confidence: 99%
“…Although in most cases these effects were observed only in transient-transactivation assays and biological consequences were not investigated or could not be detected (10), transgenic studies also implicate SUMO modification in transcriptional repression (34). Gain-of-function experiments in Caenorhabditis elegans (6) and Xenopus laevis (46) further suggest that SUMO modification can also modulate transcription factor activity in developmental processes.…”
mentioning
confidence: 99%